KNOWLEDGE MANAGEMENT IN THE IRAQI TOURISM SECTOR: FROM THE POINT OF VIEW OF THE SIX KNOWS KNOWLEDGE MODEL - Mohsin, Dr. Sabah R.; AL-Shahrabally, Inam Ali Tawfiq; alwhb Jaber, Maidean Abad (International Journal of Psychosocial Rehabilitation, 2020)
Organizations today are in an endless struggle to differentiate themselves from their competitors. Globalization, technological development, increasingly rapid diffusion of new technology and many other factors have forced organization to compete in very though, complex and challenging environment. At the same time, the transition to a knowledge society and a global knowledge economy , which is recognized as the most important social and economic change to happen in the Twenty- First century , has led to the growing importance of knowledge work and increased the demand for innovative and knowledge-intensive product , and services as the primary key to growth (1) .In this context data consists of raw facts and information is a collection of facts organized in such a way that they have an additional value beyond the value of the facts themselves.